Männyn kasvun ja puuaineen ominaisuuksien sekä saheiden laadun mallintaminen metsänhoitoon liittyen - Ikonen, Veli-Pekka (Metsäntutkimuslaitos, 2008)
Seloste väitöskirjasta: Ikonen, V.-P. 2008.Modelling the growth and properties of stem and wood of Scots pine (Pinus sylvestris L.) as related to silvicultural management with implications for sawing yield and properties of sawn pieces. Dissertationes Forestales 65.
Väitöskirjaseloste